On the Mexican ricinuleids: a new species of the genus Pseudocellus (Arachnida: Ricinulei: Ricinoididae) from the cloud forest of Chiapas, Mexico - Alejandro Valdez-Mondragón; Mayra R. Cortez-Roldán; Emmanuel F. Campuzano-Granados (Revista Mexicana de Biodiversidad)
A new species of epigean ricinuleid of the genus Pseudocellus Platnick, 1980 is described from a cloud forest of the state of Chiapas, Mexico. The species is described based on adult males and females: Pseudocellus franckei sp. nov. This is the sixth species described from Chiapas, holding the highest number of ricinuleids species for the country. The total number of described species of Pseudocellus from Mexico increases to 19, having the highest number of Ricinulei worldwide.